Apicobasal polarization: epithelial form and function. - Gibson, M.C.; Perrimon, N. (Current Opinion in Cell Biology, 2003)
The structure and function of epithelial sheets generally depend on apicobasal polarization, which is achieved and maintained by linking asymmetrically distributed intercellular junctions to the cytoskeleton of individual cells. Recent studies in both Drosophila and vertebrate epithelia have yielded new insights into the conserved mechanisms by which apicobasal polarity is established and maintained during development. In mature polarized epithelia, apicobasal polarity is important for the establishment of adhesive junctions and the formation of a paracellular diffusion barrier that prevents the movement of solutes across the epithelium. Recent findings show that segregation of ligand and receptor with one on each side of this barrier can be a crucial regulator of cell-cell signaling events.